HEPATITIS B IN PREGNANT WOMEN AND THEIR NEONATAL OUTCOMES. DO VACCINES EFFECTIVELY REDUCE TRANSMISSION - SIDDIQUI , ES; ABBASI, M; DARS , AG; PURI , P; ULLAH , MI; ABDALLA , RAH (Biological and Clinical Sciences Research Journal, 2023)
Hepatitis B infection during pregnancy can have serious consequences for both the mother and her infant. This study aimed to determine the prevalence of hepatitis B infection among pregnant women and its effect on neonatal outcomes in a tertiary care hospital in Pakistan. 120 pregnant women were enrolled in the study, and their demographic and clinical data were collected. The prevalence of hepatitis B infection was 4.2% among the study population. Infants born to hepatitis B-positive mothers were more likely to be premature and have low birth weight. Results showed that the prevalence of hepatitis B infection among pregnant women in the study population was 4.2%. Infants born to hepatitis B-positive mothers were more likely to be premature and have low birth weight. However, timely vaccination significantly reduced the transmission of hepatitis B from mother to child. In conclusion, hepatitis B infection during pregnancy can have serious consequences for both the mother and infant. This study emphasizes the importance of screening pregnant women for hepatitis B and implementing timely vaccination programs to reduce transmission and prevent adverse neonatal outcomes associated with maternal hepatitis B infection.